Juridical Study of Legal Protection of Child Victims of Sexual Violence - Athalia Shafa Putri Aninda; Taufiq Nugroho (Universitas Muhammadiyah Surakarta, 2023)
Sexual violence against children is a serious problem in Indonesia that can have long-term detrimental impacts on victims. This article aims to analyze legal protection for child victims of sexual violence from a juridical perspective. Through a study of relevant literature and journals, this article describes the meaning of sexual violence against children, the impact and consequences for victims, existing legal protection, as well as the obstacles and challenges faced in implementing this legal protection. In its analysis, this article reveals that sexual violence against children includes various acts involving coercion or sexual abuse of minors. The impact is physically, emotionally and psychologically devastating for the victim, which can continue into adulthood. Legal protection for child victims of sexual violence is based on national and international legal frameworks, which guarantee children's rights and provide legal instruments to uphold justice. However, the implementation of legal protection for child victims of sexual violence is faced with complex obstacles and challenges. Some of the main challenges include low public awareness, lack of access to adequate support services, limited resources, low capacity of law enforcement agencies, and justice processes that require a more sensitive understanding of children. To overcome this challenge, this article recommends efforts to increase public awareness, strengthen legal systems and policies, increase the capacity of law enforcement agencies, and increase victims' access to support services. With these steps, it is hoped that legal protection for child victims of sexual violence can be improved, victims receive justice, and prevention of sexual violence against children becomes a priority that is implemented comprehensively and sustainably. Increasing public awareness, strengthening the legal system, increasing the capacity of law enforcement agencies, and increasing victims' access to support services will play an important role in protecting children from sexual violence and creating a safe environment for their future.